Introduction to Fluid Mechanics - Nakayama, Yasuki, author 649504; ScienceDirect (Online service) 7722 (San Diego : Butterworth-Heinemann, 2018)
Introduction to Fluid Mechanics, Second Edition, uses clear images and animations of flow patterns to help readers grasp the fundamental rules of fluid behavior. Everyday examples are provided for practical context, before tackling the more involved mathematic techniques that form the basis for computational fluid mechanics. This fully updated and expanded edition builds on the author’s flair for flow visualization with new content. With basic introductions to all essential fluids theory, and exercises to test your progress, this is the ideal introduction to fluids for anyone involved in mechanical, civil, chemical, or biomedical engineering.